Transurethral incision versus transurethral resection of the prostate in small prostatic adenoma: Long-term follow-up - O. Abd-El Kader; K. Mohy El Den; A. El Nashar; A. Hussein; E. Yehya (African Journal of Urology, 2012)
Objectives: To evaluate the efficacy of transurethral incision of the prostate (TUIP) compared to transurethral resection of the prostate (TURP) in patients with small benign prostate adenoma, based on long-term follow-up. Patients and methods: We prospectively randomized 86 men with bladder outlet obstruction symptoms caused by a prostate less than 30 g to undergo TUIP or TURP. The following preoperative parameters were evaluated: prostate weight, international prostate symptom score (IPSS), voided volume, maximum flow rate (Qmax) and post-void residual volume (PVR). Postoperatively the patients were followed up for 48 months and the following data were collected: morbidity, operative time, catheterization period, hospital stay, Qmax, IPSS, voided volume, PVR and reoperation rate. Results: A total of 80 of the 86 patients completed the study: 40 patients in each group. The mean age of patients in group I (TURP) and group II (TUIP) was 63.6 and 66.2 years, respectively. Preoperative parameters in both groups showed no statistically significant differences with regard to uroflow parameters and prostate weight. At 48 months follow-up the mean voided volume increased from 161 ml to 356 ml in group I and from 161 ml to 341 ml in group II, Q-max increased from 8.4 to 18.4 in group I and 8.4 to 16.6 in group II, the IPSS decreased from 19 to 5.8 in group I and from 19 to 6.3 in group II and PVR decreased from 107 ml to 20 ml in Group I and from 109 ml to 21 ml in Group II (all differences statistically significant). Comparing groups I and II there were statistically significant differences with regard to mean operative time (60.0 versus 20.6 min), duration of catheterization (3.2 versus 2.2 days), hospital stay (3.7 versus 2.6 days), and the incidence of postoperative retrograde ejaculation (52.5% versus 22.5%) and erectile dysfunction (20% versus 7.5%). Conclusion: TUIP and TURP for small prostatic adenoma of less than 30 g are equally effective in providing symptomatic improvement. TUIP is more advantageous with to side-effects, operative time, hospital stay and the duration of catheterization.